Role of the Botoh as Political Brokers and Gamblers during the Tulungagung Local Election of 2018 - Abiyyu, Mohammad Darry (Jurnal Politik, 2020)
Current studies on the botoh generally focus on gambling in village-head elections (pilkades) and how its role transforms from pilkades to local elections (pilkada). However, this article defines the botoh as a political broker and gambler during the 2018 local election of Tulungagung Regency. This research found that the botoh’s way of persuading voters had a positive effect on an unfavorable candidate and helped him win. This study conducted in-depth interviews of “big” botoh, observed field operation patterns, and collected documents from related parties. The practice of gambling during pilkada is categorized into three types: ngapit, leg-leg’an, and biting. This article argues that the roles of the botoh as a political broker and gambler are caused by high-stakes gambling, compensation from candidates to be part of the campaign team, and the direct election process. In this context, candidates are likely to entrust the botoh with an important role within their campaign teams, because they are considered to understand the characteristics of voters.